Heart rate variability in patients with acute ST-segment elevation myocardial infarction after COVID-19 - V. P. Mikhin; O. A. Osipova; A. I. Gindler; A. S. Brizhaneva; N. V. Zaikina; M. P. Zaikina; T. A. Nikolenko; V. V. Savelyeva; M. A. Chernyatina (Кардиоваскулярная терапия и профилактика)
Aim. To compare heart rate variability parameters in patients after a coronavirus disease 2019 (COVID-19) with acute ST elevation myocardial infarction (STEMI) during the inhospital and post-hospital periods.Material and methods. A total of 140 patients with STEMI were divided into 2 groups: I — patients with STEMI who had COVID-19 (n=52) in the period of 1,5-6 months before acute coronary syndrome, II — comparison group (n=88), which included patients with STEMI without prior COVID-19. All patients underwent infarct-related artery stenting within the first 24 hours from the onset. Heart rate variability (HRV) parameters were determined for all patients on days 2-3 and days 9-11 and 6 months after the hospitalization for STEMI.Results. Patients in group I showed more pronounced changes in HRV indicators on days 2-3 of STEMI: RMSSD (root square of successive RR intervals) by 21% (p=0,026), variations (Var) (the difference between the minimum and maximum RR intervals) by 33% (p=0,013), VLF (total very low-frequency HRV) by 7% (p=0,009) were higher, and HF (highfrequency HRV) by 40% (p=0,003), pNN50% (ratio of the number of consecutive RR interval pairs differing by >50 ms to the total number of RR intervals) by 66% (p=0,038) were lower than in the control group, respectively. On days 9-11 of the disease in patients with a history of STEMI and COVID-19, in contrast to the control group, there was a more pronounced increase in the SDNN (standard deviation of RR intervals) by 46% (p=0,005), VLF by 42% (p=0,031), whereas in the control group there were an increase of only 22% (p=0,004) and 11% (p=0,022), respectively. The HF value in the main group increased by 25% (p=0,007), while in the control group it decreased by 19% (p=0,030). Six months after STEMI in the main group, the RMSSD decreased by 19% (p=0,009), Var by 16% (p=0,041), VLF by 30% (p=0,025), LF (low-frequency component HRV) by 11% (p=0,005), while the control group these parameters decreased by 20% (p=0,006), 21% (p=0,001), 9% (p=0,011), and 7% (p=0,016), respectively.Conclusion. In patients with STEMI and prior COVID-19, the initial HRV values differ from similar HRV parameters in patients with STEMI without prior COVID-19. In the hospital and post-hospital periods, the changes of HRV in patients with and without COVID-19 are multidirectional as follows: pronounced sympathetic hyperactivity predominates, and slower recovery of HRV in patients after COVID-19 predominates.